Endoscopic Cholecystoduodenostomy With Lumen-Apposing Metal Stent for Bile Duct Stricture in a Child with Neuroblastoma: A Case Report - Cipriani, Maria Stella; Piro, Liliana; Palo, Federico; Chiaro, Andrea; Sorrentino, Stefania; Gandullia, Paolo; Parodi, Andrea; Avanzini, Stefano (European Journal of Pediatric Surgery Reports, 2025)
We report the use of endoscopic cholecystoduodenostomy in a 6-year-old child to manage postanastomotic stricture of the common bile duct (CBD) secondary to an intraoperative injury sustained during the resection of an abdominal neuroblastoma (NB). The patient was diagnosed with stage M NB, characterized by dissemination to the bone marrow and vertebrae, and MYCN amplification. Following multiple cycles of chemotherapy and subsequent hematopoietic stem cell transplantation, the patient was scheduled for surgical resection. Preoperative imaging identified several image-defined risk factors, including infiltration of the porta hepatis and of the duodenopancreatic complex. During the dissection of the tumor, an incidental injury to the CBD occurred, which was subsequently repaired via end-to-end anastomosis. Seven months postoperatively, the patient presented with obstructive jaundice due to an anastomotic stricture, which was successfully managed through the placement of an endoscopic ultrasound-guided lumen-apposing metal stent (LAMS) between the dilated gallbladder and the duodenum. In our experience, endoscopic cholecystoduodenostomy constitutes a novel approach for addressing postoperative iatrogenic CBD strictures in pediatric patients. Further research is warranted to elucidate its benefits and risks as well as to evaluate its long-term efficacy and potential for broader application.
Keywords: case report; neuroblastoma; common bile duct injury; cholecystoduodenostomy; endoscopy